2021
DOI: 10.1038/s41588-021-00852-9
|View full text |Cite
|
Sign up to set email alerts
|

The trans-ancestral genomic architecture of glycemic traits

Abstract: Glycemic traits are used to diagnose and monitor type 2 diabetes, and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here, we aggregated genome-wide association studies in up to 281,416 individuals without diabetes (30% non-European ancestry) with fasting glucose, 2h-glucose post-challenge, glycated hemoglobin, and fasting insulin data. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
319
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 466 publications
(374 citation statements)
references
References 100 publications
5
319
0
Order By: Relevance
“…Secondly, our findings are based on data from GWAS conducted in subjects of European ancestry. Hence, our results and conclusions might not extend to other ethnic populations although, evidence from a recent, large, ancestrally diverse GWAS meta‐analysis of glycaemic traits suggests that similar results might also be expected (Chen et al, 2021 ). Thirdly, two‐sample MR studies assume that the SNP‐exposure (in this case LTL) associations are also present in the outcome dataset(s).…”
Section: Discussionmentioning
confidence: 50%
“…Secondly, our findings are based on data from GWAS conducted in subjects of European ancestry. Hence, our results and conclusions might not extend to other ethnic populations although, evidence from a recent, large, ancestrally diverse GWAS meta‐analysis of glycaemic traits suggests that similar results might also be expected (Chen et al, 2021 ). Thirdly, two‐sample MR studies assume that the SNP‐exposure (in this case LTL) associations are also present in the outcome dataset(s).…”
Section: Discussionmentioning
confidence: 50%
“…However, due to advances in GWAS methods, populations with mixed genetic backgrounds can now be included in GWAS to obtain accurate estimates of SNP effects, boost power, and improve fine-mapping of effects by leveraging linkage disequilibrium differences (Asimit et al 2016 ; Atkinson et al 2020 ). Beside the general benefits to gene discovery studies, the inclusion of diverse genetic backgrounds will improve our understanding of genetic liability across diverse populations, as demonstrated for example in a study of glycemic traits (Chen et al 2021 ), where 30% of the participants were of non-European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, efforts to jointly analyse different genetic datasets from populations of diverse ancestry have become more widespread [5,6]. These multi-ancestry genetic analyses boost power for new locus discovery, provide the opportunity to test for widespread replication of signals across independent populations and allow exploration of the genetic architecture of phenotypes across ancestries.…”
Section: Genome-wide Multi-ancestry Genetic Analysesmentioning
confidence: 99%
“…Often the variant identified from combined multi-ancestry analysis does not meet stringent genome-wide significance thresholds in individual contributing ancestries but there is still evidence that it captures a proportion of the heritability of that trait in that ancestry (Fig. 2) [2,[4][5][6]. Specifically, a recent study by the Meta-Analysis of Glucose and Insulin-related traits Consortium (MAGIC), which included 30% non-European ancestry participants, showed that including lead variants identified from the meta-analysis across ancestries in a genetic score captured more of the trait variance than the more limited set of variants that met stringent genome-wide significant thresholds in that population (Fig.…”
Section: Portability Of Signals Across Populationsmentioning
confidence: 99%
See 1 more Smart Citation